C-MYC Protein Expression and High Ki-67 Proliferative Index are Predictives of Disease Relapse in Diffuse Large B Cell Lymphoma - El-Hussien, Mahmoud Tag; Mokhtar, Nadia; Khorshed, Eman Naguib (Asian Pacific Journal of Cancer Biology, 2021)
Objective: To evaluate the status of C-MYC protein expression and Ki-67 proliferative index and to clarify their role in predicting relapse of diffuse large B cell lymphoma (DLBL). Materials and Methods: A retrospective study conducted on 50 cases diagnosed as DLBL in a 3 years’ time period from January 2014 till December 2016, collected from the archive of Pathology Departments of the National Cancer Institute Cairo - Egypt, Misr University for Science and Technology and private labs of authors. The diagnosis of DLBL for all cases, both nodal and extranodal, was confirmed by histopathologic examination and immunophenotyping. Automated immunohistochemical staining using antibodies against C-MYC protein and MIB-1 was used to evaluate the C-MYC expression in tumor cells and to assess their proliferative ability by calculating Ki-67 labelling index. The relation between the percentage of C-MYC protein expression, Ki-67 proliferative index, clinical data and the relapse status during the follow up period were analyzed. Results: A total of 50 cases of DLBL in both nodal and extra-nodal sites were included. Twenty-three cases (46%) were expressing the C-MYC protein, and 29 cases (58%) showed high Ki-67 proliferative index. Twenty-two cases (44%) relapsed during the follow-up period. Positive C-MYC protein expression was significantly associated with high Ki-67 proliferative index. C-MYC protein expression and high Ki-67 proliferative index were independently associated with disease relapses in 81.8% and 86.4% of cases respectively. Cases with combined C-MYC protein expression and high Ki-67 proliferative index showed statistical prediction of relapse in 81.8% of cases. Conclusion: C-MYC protein expression and high Ki-67 proliferative index were independently associated with relapse of diffuse large B cell lymphoma. Furthermore, the combined positive C-MYC protein expression and high Ki-67 proliferative index is better than a single positive test in predicting relapses among DLBL patients.